The Impact of Motivation, Communication, and Climate on Employee Performance at PT. Cendrawan Nusantara - Saputra, Nopa Dwi; Anggraini, Rafikha; Triono, Triono (Revenue Journal: Management and Entrepreneurship, 2025)
In contemporary organizational settings, understanding the drivers of employee performance is crucial. This research explores the relationship between intrinsic motivation, effective communication strategies, and a supportive work environment on the performance of employees at PT. Cendrawan Nusantara. Employing a mixed-method approach, this study integrates qualitative interviews and quantitative surveys, involving 77 employees over the period 2022-2023. Unlike previous studies, this research applies the Herzberg's Two-Factor Theory to motivation and uses Shannon and Weaver’s Model of Communication to examine communication strategies. Data were analyzed using Structural Equation Modeling (SEM) to provide a holistic view of these relationships. Results reveal that intrinsic motivation is a principal factor affecting performance, as it enhances employees' goal orientation and work satisfaction. Effective communication strategies, particularly those that promote transparency and feedback, significantly improve performance by fostering trust and collaboration. A positive organizational climate, characterized by inclusivity and recognition, also enhances performance. The findings underscore the importance of leadership commitment in cultivating an environment that promotes these factors. Data collection was achieved through structured interviews and online questionnaires, ensuring diverse and comprehensive feedback. This study contributes to organizational behavior literature by highlighting the synergy between motivation, communication, and climate in driving performance. Such insights can guide management practices in optimizing employee potential.